Minimizing exposure to radiation in invasive cardiology using modern dose‐reduction technology: Evaluation of the real‐life effects. Issue 7 (1st September 2017) - Faroux, Laurent; Blanpain, Thierry; Nazeyrollas, Pierre; Tassan‐Mangina, Sophie; Herce, Benoît; Tourneux, Christophe; Metz, Damien
Abstract: Objectives: We aimed to measure the reduction in the estimated dose of radiation received by patients that can be achieved using dose‐reduction technology (ClarityIQ, Philips Healthcare, The Netherlands), among all patients undergoing invasive cardiology procedures. Background: Medical procedures remain the primary source of exposure to ionizing radiation in the general population. Methods: The study population comprised all patients (without exclusion criteria) undergoing invasive coronary procedures over a 1‐year study period in a large referral centre equipped with two catheterization laboratories (cathlabs). Both cathlabs (A and B) were equipped with the Allura Xper FD10 imaging system (Philips Healthcare, The Netherlands), but only Cathlab B was equipped with ClarityIQ technology. The primary endpoint was the estimated total dose of radiation received by the patient, as assessed by Air Kerma (AK) and dose area product (DAP). Results: In total, 2095 invasive coronary procedures were analyzed. The patients who underwent procedures in Cathlab B received an average estimated dose that was 23% (AK) and 43% (DAP) lower than the dose received by patients undergoing procedures in Cathlab A ( P  < .0001). The reduction remained significant by multivariate analysis after adjustment for total X‐ray time, body mass index, arterial approach, PCI of at least one lesion, sex, and patient age. Conclusion: In our study, the ClarityIQ technology reduced the estimated radiation dose received by patients by 23‐43%, according to the method of measurement.